EFFECT OF AIR CONDITION ON AP-1000 CONTAINMENT COOLING PERFORMANCE IN STATION BLACK OUT ACCIDENT - Tjahjono, Hendro (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2015)
EFFECT OF AIR CONDITION ON AP-1000 CONTAINMENT COOLING PERFORMANCE IN STATION BLACK OUT ACCIDENT. AP1000 reactor is a nuclear power plant generation III+ 1000 MWe which apply passive cooling concept to anticipate accidents triggered by the extinction of the entire supply of electrical power or Station Black Out (SBO). In the AP1000 reactor, decay heat disposal mechanism conducted passively through the PRHR-IRWST and subsequently forwarded to the reactor containment. Containment externally cooled through natural convection in the air gap and through evaporation cooling water poured on the outer surface of the containment wall. The mechanism of evaporation of water into the air outside is strongly influenced by the conditions of humidity and air temperature. The purpose of this study was to determine the extent of the influence of the air condition on cooling capabilities of the AP1000 containment. The method used is to perform simulations using Matlab-based analytical calculation model capable of estimating the power of heat transfered. The simulation results showed a decrease in power up to 5% for relative humidity rose from 10% to 95%, while the variation of air temperature of 10 °C to 40°C, the power will decrease up to 15%. It can be concluded that the effect of air temperature increase is much more significant in lowering the containment cooling ability compared with the increase of humidity.